Practice and Economics of Freshwater Prawn Farming in Seasonally Saline Rice Field in Bangladesh - Hasanuzzaman, A.F.Md.; Rahman , M.A.; Islam, S.S. (Mesopotamian Journal of Marine Sciences, 2022)
This paper evaluates the production pattern and economics of freshwater prawn (Macrobrachium rosenbergii) farming in seasonally saline rice fields in Bangladesh. The reconnaissance survey was conducted on 30 rice-prawn ghers (RPG) in south-west region of Bangladesh. The farmers were found to use their rice fields for farming prawn and rice (aman) concurrently from April/May to January, and for only rice (boro) from January to April. In the RPG farming system, farmers use rain water during wet season, and underground water with salinity of 1-5 ‰ during dry season. The average production of prawn, aman, and boro was recorded as 439.79±90.46, 3155.48±397.33, 4778.54±389.37 kg/ha/yr, respectively. The economic analysis show potentially good return, and the net return and benefit-cost ratio were US$ 1078.35 and 1.25, respectively. The payback period was determined as 9.37 years. The study implies that the culture of prawn in seasonally saline paddy field is economically viable.